Development and Validation of the Jakarta Post-Infectious Neurological Complication Risk Score (JPINCoRS) for Children - Fatimah Mursyid; Husin Sastranagara; Rheina Weisch Fedre; Daphne Marshall (Sriwijaya Journal of Neurology, 2025)
Introduction: Post-infectious neurological complications (PINCs) in children represent a significant burden, particularly in developing countries like Indonesia. The early identification of high-risk children is crucial for timely intervention and resource allocation. We aimed to develop and validate a clinically applicable risk stratification score for PINCs in a Jakarta-based pediatric population. Methods: A prospective cohort study was conducted at three major tertiary hospitals in Jakarta, Indonesia, between January 2020 and December 2022. Children aged 1 month to 18 years admitted with a primary infectious diagnosis were eligible. Potential risk factors were collected through detailed medical history, physical examination, and laboratory investigations. The primary outcome was the development of a PINC, defined as any new neurological deficit persisting for at least 24 hours after the acute infectious phase, and categorized using a modified Rankin Scale (mRS). Multivariable logistic regression was used to identify independent predictors and develop the Jakarta Post-Infectious Neurological Complication Risk Score (JPINCoRS). Results: A total of 1250 children were enrolled, with 188 (15.0%) developing a PINC. The final JPINCoRS model included six independent predictors: (1) Type of infection (Central Nervous System [CNS] infection: odds ratio [OR] 4.5, 95% CI 3.2-6.3; Systemic infection with sepsis: OR 2.8, 95% CI 1.9-4.1), (2) Duration of fever >5 days (OR 2.2, 95% CI 1.5-3.2), (3) Presence of seizures during the acute infection (OR 3.5, 95% CI 2.4-5.1), (4) Altered mental status (Glasgow Coma Scale [GCS] <13) at admission (OR 3.0, 95% CI 2.1-4.3), (5) Thrombocytopenia (platelet count <100 x 10^9/L) (OR 1.9, 95% CI 1.3-2.8), and (6) Elevated C-reactive protein (CRP) >50 mg/L (OR 2.1, 95% CI 1.4-3.0). The JPINCoRS demonstrated good discrimination (area under the receiver operating characteristic curve [AUC] = 0.85, 95% CI 0.82-0.88) and calibration. Risk categories were defined as low (0-3 points), moderate (4-7 points), and high (8-12 points), with corresponding PINC rates of 3.5%, 18.2%, and 48.6%, respectively. Internal validation confirmed the model's robustness. Conclusion: The JPINCoRS is a simple, clinically applicable tool for predicting PINCs in children in Jakarta, Indonesia. It can aid clinicians in identifying high-risk patients who may benefit from closer monitoring, neuroimaging, and early intervention strategies. Further external validation in other settings is warranted.